The impact of carbohydrate quality on gut health: Insights from the NHANES. - Lanshuo Hu; Xuanchun Huang; Shan Liu; Lihui Fang; Jiaqi Zhang; Xudong Tang (PLoS ONE)
Background High- and low-quality carbohydrate diets are linked to gut health. However, their specific relationship with constipation or diarrhea is unclear. This study uses 2005-2010 NHANES data to examine the relationship between carbohydrate quality and constipation and diarrhea, and to identify suitable populations for different carbohydrate diets. Methods Chronic constipation was defined as BSFS types 1 and 2, and chronic diarrhea as types 6 and 7. Dietary intake data were provided by the FPED, using data from the NHANES database. Subjects recalled foods and beverages consumed in the past 24 hours, and intake was averaged and divided into quartiles (Q). After adjusting for covariates, associations between high- and low-quality carbohydrate diets and constipation or diarrhea were assessed using weighted RCS curves and multivariate logistic regression. Results were expressed as weighted ORs and 95% CIs, with subgroup analyses performed. Results A total of 11,355 people participated, with 10,488 in the constipation group and 10,516 in the diarrhea group. Multiple regression showed that high-quality carbohydrates were negatively associated with constipation (OR: 0.852, 95% CI: 0.796-0.912, P = 0.0001). Low-quality carbohydrates were positively associated with constipation (OR: 1.010, 95% CI: 1.002-1.018, P = 0.0295). There was no significant direct association between carbohydrate quality and diarrhoea (P = 0.5189, P = 0.8278). Segmented regression results showed a non-significant association between low quality carbohydrate intake above 40.65 servings/day and constipation, while quality carbohydrate intake above 3.84 servings/day was not significantly associated with diarrhoea. Subgroup analyses showed differences in carbohydrate quality and constipation or diarrhoea across populations. Conclusions High-quality carbohydrates lowered constipation risk by 33.7% and reduced diarrhea risk with intake up to 3.84 servings/day. In contrast, low-quality carbohydrates increased constipation risk by 83.4%, with risk stabilizing beyond 40.65 servings/day. These effects varied across groups, suggesting that better carbohydrate quality supports gut health, especially in sensitive individuals.